Prevalence and Description of Palliative Care in US Nursing Homes: A Descriptive Study. (March 2016) - Lester, Paula E.; Stefanacci, Richard G.; Feuerman, Martin
Objective: To describe rates and policies in U.S. Nursing Homes (NH) related to palliative care, comfort care, and hospice care based on a nationwide survey of directors of nursing. Measurements: A national survey was distributed online and was completed by 316 directors of nursing of NHs (11% response rate). The directors of nursing were asked about availability and policies in their facilities. Specifically, questions were related to policies, referral patterns, discussion about such care, and types of medical conditions qualifying for such services. Results: Hospice is significantly more available than palliative or comfort care programs; also, for-profit facilities, compared to non-profits, are significantly more likely to have palliative care programs and medical directors for palliative care. Social workers and nurses were most likely to suggest palliative type programs. Only 42% of facilities with palliative program provide consultation by a palliative certified physician. Residents with non-healing pressure ulcers, frequent hospitalizations, or severe/uncontrolled pain or non-pain symptoms were less likely to be referred. Conclusions: There is limited availability of palliative type programs in NH facilities and underutilization in those NH with programs.